Democrazia e rappresentanza politica - Salvatore, Curreri (Firenze University Press, 2004)
During the 13th Legislature of the Italian Republic the phenomenon of parliamentary mobility, that is of the passage of MPs and Senators from one political group to another, assumed significant dimensions in terms both of the number of representatives involved, and in terms of quality, in view of the creation of governments through the decisive contribution of deserter MPs, sometimes joined together in specially created groups. The aim of the work is to review the principles of political representation, retracing their genesis and their translation in the constitutional and legislative arena and in parliamentary regulations, testing the viability of the traditional reconstructions of the national representation of the parliamentarian.